2019
DOI: 10.3390/nano9030380
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization Procedure for Temperature-Sensitive Hydrogels Loaded with Silver Nanoparticles for Clinical Applications

Abstract: Hydrogels (HG) have recognized benefits as drug delivery platforms for biomedical applications. Their high sensitivity to sterilization processes is however one of the greatest challenges regarding their clinical translation. Concerning infection diseases, prevention of post-operatory related infections is crucial to ensure appropriate patient recovery and good clinical outcomes. Silver nanoparticles (AgNPs) have shown good antimicrobial properties but sustained release at the right place is required. Thus, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…However, it can be very costly thus mitigating its wide utilization. Conventional UV or heat treatments are also hindered by the sensitive nature of hydrogel technology (i.e., inducing degradation and impacting gelation behaviors) [170]. Fortunately, recent studies have demonstrated that steam-sterilization and gamma-irradiation minimally impact mechanical properties of HA, poloxamer, and gelatin-based hydrogels [171,172].…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be very costly thus mitigating its wide utilization. Conventional UV or heat treatments are also hindered by the sensitive nature of hydrogel technology (i.e., inducing degradation and impacting gelation behaviors) [170]. Fortunately, recent studies have demonstrated that steam-sterilization and gamma-irradiation minimally impact mechanical properties of HA, poloxamer, and gelatin-based hydrogels [171,172].…”
Section: Discussionmentioning
confidence: 99%
“…The size and composition of the nanoformulations offer major challenges while the selection of sterilization technique before it is administered to the body. Sterilization techniques like gamma irradiation or autoclaving offer high risk to nanomedicines, especially when one of the components is biological material [70]. In case of liposomal nanomedicines, where the particle structure is malleable or flexible, conventional sterilization filters with average particle size well below 220 nm, may be suitable [71].…”
Section: Sterility or Functionality: What Is At Stake?mentioning
confidence: 99%
“…Rafael et al (2019) [ 62 ] produced and characterized thermo-sensitive HGs based on Pluronic ® F127 loaded with AgNPs. Dry heat methods affected the quality of these nanoparticles but not the autoclaving methods.…”
Section: Sterilization Of Ophthalmic Nanopharmaceuticalsmentioning
confidence: 99%
“…The formation of reactive oxygen species reached higher values of peroxides when sterilized by dry heat than by autoclaving. The sterilization of the polymer prior to the HG formation led to the formation of peroxides [ 62 ]. The presence of AgNPs did not affect the gelation behavior when compared to the sterilized unloaded HG, but it has been proven that temperature can change the mechanical properties of the hydrogels.…”
Section: Sterilization Of Ophthalmic Nanopharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation